A miniature magneto-rheological actuator with an impedance sensing mechanism for haptic applications. (June 2014) - Yang, Tae-Heon; Koo, Jeong-Hoi; Kim, Sang-Youn; Kwon, Dong-Soo
This article presents a miniature haptic actuator (or haptic button) based on magneto-rheological fluids, designed to convey realistic and vivid haptic sensations to users in small electronic devices. The haptic sensation, which is generated in the form of resistive force, should vary according to the stroke of the actuator (or the pressed depth of its plunger). Thus, a sensing method for gauging the stroke should be integrated into the proposed magneto-rheological actuator to demonstrate real-world haptic applications. To determine the pressed depth of the magneto-rheological actuator, this article proposes an impedance sensing mechanism. The proposed sensing method measures the impedance change of the solenoid coil built in the actuator in the form of voltages to estimate the pressed depth. A control system was constructed to evaluate the simultaneous sensing and actuating performance of the proposed. The results show that the sensitivity of the proposed sensing method is sufficient to regulate the output resistive force over the small stroke range of the actuator. The results further show that the controller with the proposed sensing method enables users to measure the displacement of the plunger and concurrently generate resistive forces to convey haptic sensations to users without additional sensors.